School Climate, Deployment, and Mental Health Among Students in Military-Connected Schools. Issue 1 (January 2018) - De Pedro, Kris Tunac; Astor, Ron Avi; Gilreath, Tamika D.; Benbenishty, Rami; Berkowitz, Ruth
Research has found that when compared with civilian students, military-connected students in the United States have more negative mental health outcomes, stemming from the stress of military life events (i.e., deployment). To date, studies on military-connected youth have not examined the role of protective factors within the school environment, such as school climate, in the mental health and well-being of military-connected adolescents. Given this gap in the research on military adolescents, this study draws from a large sample of military and non-military secondary adolescents in military-connected schools ( N = 14, 943) and examines associations between school climate, military connection, deployment, and mental health. Findings show that multiple components of school climate are associated with a lower likelihood of depressive symptoms and suicidal ideation and increased likelihood of well-being among students in military-connected schools, after controlling for student demographics, military connection, and deployments. The authors conclude with a discussion of school climate interventions for military-connected youth.